Infectious Diseases and Arthropods - Goddard, Jerome (Infectious Disease, 2018)
With the exception of a few tropical medicine schools worldwide, current medical education programs include almost zero discussion of the interface between infectious diseases and entomology. That is why this book was initially published in the first edition almost 17 years ago. The third edition of this valuable infectious disease entomology book updates all existing chapters with the newest scientific developments described in the medical and entomological literature in addition to covering 10 entirely new topics not addressed in previous editions, which include: · arthropod identification controversies · early beginnings of public health and disease control · red-meat allergy · updates on vaccine development for dengue and malaria · discussion of Chikungunya and Zika viruses · American Boutonnneuse Fever · the newest controversies in Lyme disease · recent findings of viruses in ticks · bed bug bite reactions · Morgellons disease (an imaginary infectious disease).